1987
DOI: 10.1002/ana.410220418
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in multiple sclerosis: Decreased signal in thalamus and putamen

Abstract: High-field strength (1.5 Tesla) magnetic resonance imaging in 15 patients with multiple and extensive white-matter lesions and clinically definite multiple sclerosis delineated a previously undescribed finding of abnormally decreased signal intensity on T2-weighted images in the thalamus and putamen. The decreased signal intensity (preferential decreased T2 relaxation time) is most likely to be related to abnormally increased iron accumulation causing local magnetic field heterogeneities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…ventional MR images in MS. Drayer et al, 16 in 1987, observed hypointensity on conventional MR imaging in the deep gray matter regions in MS, in which the decreased signal intensities were presumed to be from iron content. However, their findings were contradictory to those by Grimaud et al, 29 who reported that only a mild degree of low signal intensity in the thalamus and low signal intensity in the basal ganglia are rarely seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ventional MR images in MS. Drayer et al, 16 in 1987, observed hypointensity on conventional MR imaging in the deep gray matter regions in MS, in which the decreased signal intensities were presumed to be from iron content. However, their findings were contradictory to those by Grimaud et al, 29 who reported that only a mild degree of low signal intensity in the thalamus and low signal intensity in the basal ganglia are rarely seen.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on humans, conventional T2-weighted imaging also revealed abnormal hypointense signals in lesions, the basal ganglia, thalamus, and cerebral cortex, which indicates pathologic deposition of iron possibly leading to tissue damage in MS. 15,16 Neurodegeneration of the deep gray matter may correspond to the cognitive impairment commonly observed in patients with MS. 17 These findings are important in suggesting that an abnormal deposition of iron plays a significant role in the pathophysiologic process of tissue injury in MS. Previous data analysis for iron assessment on the basis of qualitative rating judged with relative evaluation of signal intensity of structures on T2-weighted imaging may not be appropriate because of the inherent variations of signal intensity in acquisition-to-acquisition MR images.…”
mentioning
confidence: 99%
“…The T 2 hypointensity, first described by Drayer et al [2] and later by Grimaud et al [3], is supposed to reflect iron deposition and gray matter degeneration. Bakshi et al [4] analyzed signal reduction on T 2 -weighted imaging (T 2 WI) in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Since MS is primarily a disease of the white matter, basal ganglia-associated signs and symp- toms are quite rare. However, thalamic involvement has been reported in MS (7). In the present case, although differentiation of MSfrom ADEMby MRIwas difficult, because of the separation of her two episodes in time and central nervous system location, our patient should be regarded as having MSrather than ADEM.…”
Section: Discussionmentioning
confidence: 62%